The Da'wa Narration of Matchmaking in Opor Ayam Short Film - Fatimah Azzahro; Hartini Salama (LADU: Journal of Languages and Education, 2023)
Background: The narration of women as wives in every age and culture is always conveyed using various methods. This diversity is increasingly being explored through the development of media and digital technology. Short films through the Youtube channel can also be a medium of dawah to narrate a matchmaking. Purpose: The focus of this study is limited to how the topic of matchmaking is narrated in the short film “Opor Ayam” published by NU Online. Design and methods: This study’s method is descriptive qualitative with verbal and visual narrative research data on the short film Opor Ayam published by NU Online in 2021. This research uses semiotics-signification theory to obtain a narrative structure for the meaning of matchmaking. Results: The results show that the Opor Ayam film has four stages, namely equilibrium, disruption, disequilibrium and new-equilibrium as a narrative structure. The results of the discussion also show that the topic of matchmaking is conveyed as; (1) acceptable in religion, (2) must be based on religious provisions, (3) the narrative emphasizes that marriage through matchmaking is a familiarization and must be based on religion.